Microstructure and mechanical properties of C/SiC-niobium alloy (C103) joint brazed with TiCuAg alloy for aerospace applications - Kamal A.; Shukla A.K.; Shinde V.M.; Rajasekhar B.V. (My University, 2025)
In this study, niobium-based alloy C103 is joined to carbon fibre-reinforced SiC (C/SiC) composite utilising commercially available Ticusil® and Cusil® alloy braze filler material. Various characterisation techniques are employed to investigate the interfacial microstructures and evolution mechanism of C/SiC–C103 junctions. Lap shear strength (LSS) is used to evaluate the mechanical performance of the brazed joints. The results show that adding Ti promotes the growth of “nails”, a phenomenon favourable for robust joint quality. However, high Ti content deteriorates the bond strength due to the formation of significant brittle intermetallic phases, causing premature delamination of the joints. The response surface methodology (RSM) is employed to examine the interactions among various operating parameters. To attain the high LSS value, the high temperature, intermediate reaction time, and low cooling rate are necessary for a Ticusil-based joint, whereas high temperature, low reaction time, and increased cooling rate are preferred for a Cusil-based joint. © 2023 Elsevier Ltd and Techna Group S.r.l.